The Ergonomics of Caste in the Social Insects - Wilson, Edward O. (American Economic Review, 1978)
Wilson's paper is an interesting example of a current trend in evolutionary theory, in which methods of economic analysis become useful. The survival and diffusion of colonies of social insects is measured essentially by the number of virgin queens surviving. The colonies are endangered by various contingencies. The different castes in the colony have different comparative advantages in dealing with the different contingencies. Each insect in the colony imposes a cost of maintenance which may be measured roughly by its weight, and the weights differ among castes. Survival of a given number of virgin queens in the face of the different contingencies can be achieved by varying combinations of the different castes. Presumably the colony structure most fit to survive is that in which the numbers in the different castes minimize the total weight of the colony for given survival of virgin queens. This gives rise to a linear programming problem whose solution has biologically interesting implications for the degree of specialization of the different castes and for their proportions. Resource scarcity is a common characteristic of the biological world, of which humans are part. It is therefore not surprising that the same modes of analysis find applications in both biology and economics. After all, Charles Darwin has reported that the idea of natural selection came to him from a reading of Malthus. What the economist must envy in the biologist and possibly seek to emulate is the array of qualitative and quantitative data to check his or her theories and guide the development of new ones.